Discretionary Online Games and Social Skills On Children’s Aggressive Behavior - Qorina Widuri; Yufiarti Yufiarti; Hapidin Hapidin (Journal of Educational Science and Technology (EST), 2018)
This study aims to find out the influence of the intensity of playing online games and social skills toward aggressive behavior in 8 years old children using ex-post facto quantitative pathways. This study was conducted in four elementary schools in the city of Bekasi, with 120 total numbers of respondents (N) in 8 years old children who were students in grade two elementary school. This study applies treatment by level 2x2 design. The hypothesis in this study is analyzed by using two-way variant analysis (ANOVA) and Tukey Test. The results of this study shows that 1) there is a significant difference on aggressive behavior in 8 years old children who were intensive and not intensive playing online games; 2) there is a difference on aggressive behavior in 8 years old children who have high social skills and low social skills; and 3) there is a significant influence based on interaction between intensity of playing online games and social skills toward aggressive behavior in 8 years old children in the city of Bekasi.